Nebulized mesenchymal stem cell derived conditioned medium ameliorates Escherichia coli induced pneumonia in a rat model - González, Héctor E.; McCarthy, Sean D.; Masterson, Claire; Laffey, John G.; MacLoughlin, Ronan; O’Toole, Daniel (Frontiers in Medicine, 2023)
Background Mesenchymal stem cells (MSC) have shown immense therapeutic promise in a range of inflammatory diseases, including acute respiratory distress syndrome (ARDS), and are rapidly advancing through clinical trials. Among their multimodal mechanisms of action, MSCs exert strong immunomodulatory effects via their secretome, which contains cytokines, small molecules, extracellular vesicles, and a range of other factors. Recent studies have shown that the MSC secretome can recapitulate many of the beneficial effects of the MSC itself. We aimed to determine the therapeutic capacity of the MSC secretome in a rat bacterial pneumonia model, especially when delivered directly to the lung by nebulization which is a technique more appropriate for the ventilated patient. Methods Conditioned medium (CM) was generated from human bone marrow derived MSCs in the absence of antibiotics and serum supplements. Post-nebulization lung penetration was estimated through nebulization of CM to a cascade impactor and simulated lung and quantification of collected total protein and IL-8 cytokine. Control and nebulized CM was added to a variety of lung cell culture models and injury resolution assessed. In a rat E. coli pneumonia model, CM was instilled or administered by nebulization and lung injury and inflammation assessed at 48 h. Results MSC-CM was predicted to have good distal lung penetration and delivery when administered by nebulizer. Both control and nebulized CM reduced NF-κB activation and inflammatory cytokine production in lung cell culture, while promoting cell viability and would closure in oxidative stress and scratch wound models. In a rat bacterial pneumonia model, both instilled and nebulizer delivered CM improved lung function, increasing blood oxygenation and reducing carbon dioxide levels compared to unconditioned medium controls. A reduction in bacterial load was also observed in both treatment groups. Inflammatory cytokines were reduced significantly by both liquid and aerosol CM administration, with less IL-1β, IL-6, and CINC1 in these groups compared to controls. Conclusion MSC-CM is a potential therapeutic for pneumonia ARDS, and administration is compatible with vibrating mesh nebulization.